Eksplorasi Potensi Actinomycetes Penghasil Antibiotik Baru dari Danau Poso Sulawesi Tengah Sebagai Antibakteri Patogen pada Manusia - Hermin Lastri Gintoe; Riskayati; Slamet Ifandi; Andi Lindhemutianingrum Siradje (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to isolate, characterize, evaluate antibacterial activity, and identify Actinomycetes isolates at the molecular level. The method used was an experimental approach with a descriptive design. The research consisted of several stages: (1) isolation and characterization through macroscopic, microscopic, and biochemical tests, and (2) antibacterial activity testing and molecular identification of Actinomycetes isolates. The results showed that five isolates—DP1, DP2, DP3, DP4, and DP5—were identified and suspected to belong to the genus Streptomyces. Macroscopic and microscopic characterization indicated that all isolates exhibited white, yellow, and brown colony colors and were Gram-positive. Biochemical tests showed positive results for catalase, coagulase, oxidase, citrate, and TSIA tests. Antibacterial activity assays against Escherichia coli and S. aureusrevealed that isolate DP4 had the strongest inhibition zone, while showing negative activity against S. typhi. In conclusion, five Actinomycetes isolates were successfully isolated from the sediment soil of Lake Poso. Isolate DP4 demonstrated the greatest potential as an antibacterial candidate by inhibiting two pathogenic bacteria. Based on 16S rDNA sequence similarity analysis, isolate DP4 was identified as S. aurantiacus with 99% similarity. Keywords: Actinomycetes, Antibacterial, Lake Poso, Exploration